MODEL FOR CAPACITY BUILDING OF VILLAGE APPARATUS IN REALIZING DISABILITY INCLUSIVE VILLAGE (A STUDY IN MIRUK TAMAN VILLAGE, DARUSSALAM SUBDISTRICT, ACEH BESAR REGENCY) - Misbah, T. Lembong; Rusnawati, Rusnawati; Situmeang, Marini Kristina; Maisarah, Siti; Fatimah, Fatimah; Ramadhani, Desi (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2024)
This study aims to map the capacity model of the gampong apparatus in realizing disability-inclusive gampong in Miruk Taman Village, Darussalam District, Aceh Besar Regency. This research was conducted using a qualitative method with an exploratory-participatory approach and referring to emancipatory principles. The results of the study found that two strengthening models for gampong apparatus in realizing inclusive gampong were carried out through 3 phases, namely: Awareness, Empowerment, and Mentoring. The Awareness stage was carried out through workshop activities related to the importance of qanun gampong as a legal basis for realizing inclusive gampongs. Furthermore, activities were also carried out to increase the knowledge of gampong apparatus and KSM on the rights of people with disabilities facilitated by the Social Service, the Aceh Building Forum, and academics. The empowerment was carried out through assistance in the formulation of the qanun gampong together with the Head of the Aceh Besar Legal Division, the Aceh Besar Social Service, DPMG, the Aceh Building Forum as a companion institution, and academics from the Islamic Community Development Study Program of UIN Ar-Raniry until the qanun was successfully ratified. Meanwhile, the implementation of qanun is carried out through training for gampong apparatus and KSM through mapping the needs of people with disabilities, providing access to services needed by people with disabilities, and through the declaration of disability-inclusive gampong, which involves the direct participation of people with disabilities as beneficiaries. This capacity model has provided improvements in the social conditions of people with disabilities, especially access to development in Gampong Miruk Taman, where they were previously marginalized.